2005
DOI: 10.1111/j.1532-950x.2005.00084.x
|View full text |Cite
|
Sign up to set email alerts
|

A New Approach for Perineural Injection of the Lateral Palmar Nerve in the Horse

Abstract: The technique described provides an accurate and simple method for perineural injection of the lateral palmar nerve proximal to the origin of its deep branch. This technique can be used to anesthetize the lateral palmar nerve for diagnosis of pain originating in the palmaroproximal aspect of the metacarpus without risk of inadvertently desensitizing structures within the carpal synovial sheath.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 5 publications
0
34
0
2
Order By: Relevance
“…Neural anatomy of (a) the palmar aspect of the left carpus and (b) the lateral and palmar aspects of the left distal thoracic limb. Yellow cross Medial approach (Castro and others 2005), red cross Lateral approach (Wheat and Jones 1981)…”
Section: Neural Anatomymentioning
confidence: 99%
See 1 more Smart Citation
“…Neural anatomy of (a) the palmar aspect of the left carpus and (b) the lateral and palmar aspects of the left distal thoracic limb. Yellow cross Medial approach (Castro and others 2005), red cross Lateral approach (Wheat and Jones 1981)…”
Section: Neural Anatomymentioning
confidence: 99%
“…Wheat and Jones (1981) subsequently found that although penetration of the carpometacarpal joint was avoided with this procedure, penetration of the carpal sheath could occur. The ‘Castro block’ (medial approach), reported more recently by Castro and others (2005), avoids both these complications by depositing 3 to 4 ml of local anaesthetic over the lateral palmar nerve (using a 23 G 16 mm needle) as the nerve courses medial to the accessory carpal bone (Fig 2). These two blocks can be performed with the horse weight bearing.…”
Section: Perineural Anaesthesiamentioning
confidence: 99%
“…93 Of chief concern are the distal palmar/plantar outpouchings of the carpometacarpal (CMC)/tarsometatarsal (TMT) joints and their close relationship with the suspensory origin. 94,95 In the forelimb, a high lateral palmar nerve block 96,97 is the most specific perineural block for the suspensory origin and is therefore preferred to the traditional high palmar block (high 'four-point' block) or local infiltration of the suspensory origin (see Chapter 13). 98,99 A comparable technique in the hind limb involves blocking the deep branch of the lateral plantar nerve proximal to the metatarsus; 100 although the specificity of this block for proximal plantar metatarsal pain has been called into question by some.…”
Section: Diagnostic Analgesiamentioning
confidence: 99%
“…Dabei werden auch Anteile des oberflächlichen Systems anästhesiert und häufig (in 68% der Fälle) die Karpalbeugesehnenscheide unbeabsichtigt punktiert (Ford et al 1989). Dagegen wurde bei perineuraler Injektion von Methylenblau an den N. palmaris lateralis auf Höhe des Os carpi accessorium von medial eine Diffusion oder Injektion in die Karpalbeugesehnenscheide vermieden (Castro et al 2005). …”
Section: Neuroanatomieunclassified
“…Methylenblau) in verschiedenen Abschnitten der Gliedmaße des Pferdes (Ford et al 1988, Castro et al 2005, Hughes et al 2007, Nagy et al 2009, Nagy et al 2010 vor.…”
Section: Diskussionunclassified